Analisis Peran Literasi Morfologis dalam Pengembangan Kemampuan Berpikir Kritis Siswa melalui Pembelajaran Bahasa Indonesia - Ririn Meylani; Silvina Noviyanti; Nazurty; Naifa Mardati; Idha Nur Hayati; Elsa Monica Simamora; Gita Jessica Margaretha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the crucial role of morphological literacy in fostering critical thinking skills among elementary school students within Indonesian language learning. The phenomenon of Indonesia's low literacy rankings based on PISA data provides the background for the urgency of this research, suggesting a need for language structure teaching strategies that can stimulate cognitive development. Using the Narrative Literature Review (NLR) method through a qualitative approach, this research synthesizes various scientific literatures to dissect the correlation between morphological awareness and critical thinking sharpness. The findings show that morphological literacy particularly the mastery of affixation and reduplication serves as a cognitive foundation that enables students to deconstruct meaning beyond textual understanding. This analytical process toward word structure encourages the development of inferential and evaluative thinking skills, which are the main pillars of critical thinking. This study concludes that strengthening morphological literacy within contextual learning is a strategic instrument to enhance students' intellectual capacity in facing future information complexities.